(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Objective: This paper addresses the Old and New Testaments viewed from the econarrative perspective in environmental and social contexts. Method: The method applied combines the techniques of conceptual, semantic, thematic, and narrative analyses in the authors’ original interpretation. Results and discussion: It examines biblical narrations via four discourse-forming concepts – GOD, NATURE, MAN, and SOCIETY, various combinations of which shape a set of narrative ecotopics focused on the concept of MAN. Such ecotopics as "Man and nature in their interaction", "Man and family relations", "Man in society", "Man’s path to God" reveal the relationships between man, nature, God, family, and society as well as man’s responsibility before God. Their ecological component is marked by verbocentric ecodescriptors actualized in narrative schemes. Material: This study zeroes in on the narrative ecotopic "Man’s path to God" with its subtopic "the way through sacrifice", presented in the stories of Abraham in Genesis and Hannah in 1 Samuel from the Old Testament as compared to the story of Jesus in 1 Peter, 1 John, and the Gospel of John from the New Testament. Conclusions: In the Old Testament the path to God through sacrifice in ecologically charged narrations reflects the readiness of man to sacrifice his/her most valuable thing to prove their faithfulness and faith. In the New Testament Jesus’ sacrifice involves the whole humankind, thanks to His sufferings for their sinless life.